1960
DOI: 10.1002/aja.1001070203
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of oligodendrocytes in cerebral gray and white matter of several mammals

Abstract: This comparative study on the regional arrangements of oligodendrocytes, as a supplement to the preceding study on perivascular distribution (Cammermeyer, '60e), has as a main objective to point out a number of cytoarchitectonic peculiarities, as e.g., the concentration of these cells in the periphery of gray matter and the adjacent white matter. These anatomical observations may offer additional circumstantial evidence in support of the hypothesis that the oligodendrocytes occupy positions consistent with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Most interestingly, the Allen Brain Atlas, which provides gene expression data across the whole human brain, indicates highest expression of S100B in the corpus callosum in agreement with our results and in the globus pallidus in agreement with the literature [69].…”
Section: Discussionsupporting
confidence: 92%
“…Most interestingly, the Allen Brain Atlas, which provides gene expression data across the whole human brain, indicates highest expression of S100B in the corpus callosum in agreement with our results and in the globus pallidus in agreement with the literature [69].…”
Section: Discussionsupporting
confidence: 92%
“…This may also explain the increased FA within the putamen. It has been shown that the transition zone between the putamen and globus pallidus has a large concentration of oligodendrocyte in primates (Cammermeyer, 1960). …”
Section: Discussionmentioning
confidence: 99%
“…The globus pallidus which is an output structure of the basal ganglia, 154 has been shown to have large concentrations of oligodendrocytes in the transition zone between the putamen and globus pallidus in primates. 155 This could explain the predominant white matter tissue classification seen in the current globus pallidus segmentation. In light of the association between higher BMI and greater total white matter proportion in children 115 the increased globus pallidus volume seen in the GNE may be driven by the increment specific to white matter.…”
Section: Discussionmentioning
confidence: 93%